Implementasi Kurikulum Pendidikan Bahasa Arab Studi Kasus di Fak. Tarbiyah Jurusan PBA IAIN Tulungagung - Nuryani Nuryani (Ta'allum: Jurnal Pendidikan Islam, 2015)
The implementation of curriculum is a systemic process including many stakeholders. The effectiveness of a curriculum can be evaluated after it is implemented in the classroom where the teachers and the students are actively involved. The teachers, therefore, should show competency and responsibility in implementing curriculum. The current articles discusses several issues related to the implementation of curriculum in Arabic Department, namely, (1)definition of implementation, (2) definition of curriculum, (3) implementation of curriculum, (4)stages in implementing curriculum at Arabic Department.